Digital Library of the Belgrade City Library in the service of Citizen Science (Pubmet, 2025)
Citizen science allows participants to directly contribute to research, increase their understanding of science, and learn about issues facing the entire community. However, a significant concern related to practising citizen science is the ability of amateur scientists, i.e., citizen science volunteers, to provide quality and accurate data. From a societal angle, it is essential to engage with societal actors in various formats that suit participants, evaluate two-way learning outcomes, and develop the transformative role of science communication. (3) Public libraries and their digital collections have an important role in fostering citizen science. By curating and providing access to verifiable sources of information public libraries empower citizens and non-academic researchers to collaborate on research projects, thereby democratising knowledge and promoting a culture of lifelong learning and scientific inquiry.